SHARIA ANNUITIES IN PENSION PROGRAMS: LEGAL, ECONOMIC, AND FUTURE CHALLENGES - Kandiarum, Dyyah Retno; Putri, Leilani Vania; Rahmadhani , Ersa Novalia; Fauzi , Raasyid Ahmad; Waluyo, Waluyo (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to provide a comprehensive analysis of the concept, legal foundation, and implementation of Sharia annuities in retirement programs. this article will project the prospects for the development of Islamic annuities in Indonesia and globally, considering the driving and inhibiting factors of their growth, as well as the implications for the Islamic financial industry and societal welfare. The research employs a qualitative library research method by analyzing literature, DSN-MUI fatwas, and Islamic accounting standards. The findings reveal that Sharia annuities offer an Islamic-compliant retirement investment alternative that avoids riba, gharar, and maisir. The use of the annuity method in murabahah profit recognition has progressed significantly following the issuance of DSN Fatwa No. 84/DSN-MUI/XII/2012, although it still faces regulatory and accounting implementation challenges. Overall, Sharia annuities demonstrate promising prospects as a sustainable and inclusive retirement finance instrument, particularly in Muslim-majority countries like Indonesia.